2022
DOI: 10.1186/s40359-022-00826-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the factor structure and psychometric characteristics of the Arabic adaptation of the sense of coherence SOC-13 scale: a confirmatory factor analysis

Abstract: Background The sense of coherence is as focused on one’s awareness of the level of pervasive, enduring, and dynamic feelings. Stronger sense of coherence leads to better physical and mental health and promotes recovery from life stressors. Sense of coherence-13 (SOC-13) is a 13-item valid and reliable measure for individual’s healthy living. However, the factor structure of SOC-13 was criticized in several cultures and languages. The current study was set to explore the factor structure of an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
5
2
0
Order By: Relevance
“…However, certain studies, such as Rajesh et al [19] and Tang and Dixon et al [20], have reported a higher inter-item correlation for the scale when subjected to their respective populations. The first item under meaningfulness (M1) has consistently been reported to have a poor correlation with the whole construct, as reported in studies by Alharbi et al [15] and Lerdal et al [21]. This finding is in line with our observations in the study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, certain studies, such as Rajesh et al [19] and Tang and Dixon et al [20], have reported a higher inter-item correlation for the scale when subjected to their respective populations. The first item under meaningfulness (M1) has consistently been reported to have a poor correlation with the whole construct, as reported in studies by Alharbi et al [15] and Lerdal et al [21]. This finding is in line with our observations in the study.…”
Section: Discussionsupporting
confidence: 92%
“…This study adopted the SOC-13 scale not only for convenience but also since the scale has been reliable when tested in various populations (α = 0.70 to 0.92) [16]. Our study did observe a good reliability score (Cronbach's α value = 0.77), which is consistent with most studies as well as with the two other studies done in the region [14,15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CFA fit indices indicated that a one-factor structure, a bifactor structure and a correlated three-factor structure fit the data to an acceptable degree but that the one-factor model had the best fit. This aligns with Antonovsky's original conceptualization of SOC as a unidimensional construct [1] but contrasts with some prior studies that have supported a three-factor structure [10,11]. These disparate findings in the literature may be attributed to population differences or methodological variations, and the present study contributes additional insights into the factor structure of the scale.…”
Section: Discussionsupporting
confidence: 52%
“…The confirmation of three-factor structure also required correlation of the residuals of two-item pairs (Item 2 and Item 4). A validation study of an Arabic adaptation of the SOC-13 [11] stated that removal of the three reversely phrased items in the scale significantly enhanced its three-factor structure. Saravia and colleagues [12] found that the three-factor solution was a better fit than the one-factor solution in a Peruvian sample.…”
Section: Introductionmentioning
confidence: 99%